Modifying the hemagglutinin gene with the packaging signals to improve the ability of replication in eggs of IBT-RG02 vaccine virus strain - Nguyen, Chi Hung; Nguyen, Nam Trung (Vietnam Journal of Biotechnology, 2023)
The hemagglutinin (HA) and neuraminidase (NA) genes were derived from the popular H5N1 virus and the remaining six internal segments were derived from the A/Puerto Rico/8/34 strain (H1N1, PR8). However, some of these candidate strains have been reported to produce relatively low yields in vaccine manufacture does not replicate well in chicken eggs, posing an obstacle to egg-based vaccine production. To address this issue, we explored the possibility that PR8’s hemagglutinin (HA) packaging signals mediate improvement of candidate vaccine virus yield in eggs. We constructed chimeric HA genes having the coding region of IBT-RG02 HA flanked by the 50 packaging signals of PR8’s HA. The growth of candidate vaccine viruses containing the chimeric HA (RG2, RG3, RG4) was increased in embryonated chicken eggs with a nearly 1.5 to 2-fold higher titer than that of control (RG1). It is concluded that the using of chimeric HA fragment can subsequently improve the replication of reversed genetics-derived virus strains in eggs.